2022
DOI: 10.3390/v14050933
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Immune Responses in the Upper Respiratory Tract and the Infectivity of SARS-CoV-2

Abstract: Increasing evidence shows the nasal epithelium to be the initial site of SARS-CoV-2 infection, and that early and effective immune responses in the upper respiratory tract (URT) limit and eliminate the infection in the URT, thereby preventing infection of the lower respiratory tract and the development of severe COVID-19. SARS-CoV-2 interferes with innate immunity signaling and evolves mutants that can reduce antibody-mediated immunity in the URT. Recent genetic and immunological advances in understanding inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 96 publications
3
39
0
Order By: Relevance
“…This contrasts with HCoV-NL63, typically associated with the common cold and primarily upper respiratory symptoms, as well as SARS-CoV-2, which is known to cause a wide range of disease from asymptomatic infections to mild colds to severe pneumonia. It is plausible that HCoV-mediated cytotoxicity in the case of mild SARS-CoV-2 and HCoV-NL63 infections in the nasal epithelium may facilitate early viral clearance and limit the subsequent spread of viral infection to the lower airway (Ramasamy, 2022). Whereas limited cytotoxicity during MERS-CoV infection may allow for uninhibited spread to cause lower airway pathology.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with HCoV-NL63, typically associated with the common cold and primarily upper respiratory symptoms, as well as SARS-CoV-2, which is known to cause a wide range of disease from asymptomatic infections to mild colds to severe pneumonia. It is plausible that HCoV-mediated cytotoxicity in the case of mild SARS-CoV-2 and HCoV-NL63 infections in the nasal epithelium may facilitate early viral clearance and limit the subsequent spread of viral infection to the lower airway (Ramasamy, 2022). Whereas limited cytotoxicity during MERS-CoV infection may allow for uninhibited spread to cause lower airway pathology.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that when the response to respiratory viruses is inadequate the infection spreads to lower respiratory tract (LRT) 106 . An early and effective immune response in patients infected with SARS-CoV-2 can limit and eliminate the infection yet in the upper respiratory tract (URT) 107 . Genomic analyses shown that there is no tissue specific genetic adaptation of SARS-CoV-2 to the URT or LRT 108 .…”
Section: Discussionmentioning
confidence: 99%
“…For controlling SARS-CoV-2, a primary goal of current vaccines is to prevent severe infection by reducing the viral load in the lower airways (vs. in both lower and upper airways to prevent mild disease). [25][26][27] The notion of mechanistic correlates of clinical protection is supported by a study in nonhuman primates showing that levels of neutralizing activity were inversely correlated with viral replication in the upper and lower airways after a SARS-CoV-2 challenge. Importantly, protection against lower versus upper respiratory tract disease was achieved at lower serum antibody concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions of immunosuppression provide a unique opportunity to dissect the different roles of immune elements and provide a novel avenue for the protection of at‐risk and general populations. For controlling SARS‐CoV‐2, a primary goal of current vaccines is to prevent severe infection by reducing the viral load in the lower airways (vs. in both lower and upper airways to prevent mild disease) 25–27 . The notion of mechanistic correlates of clinical protection is supported by a study in nonhuman primates showing that levels of neutralizing activity were inversely correlated with viral replication in the upper and lower airways after a SARS‐CoV‐2 challenge.…”
Section: Discussionmentioning
confidence: 99%